Is the Efficiency Wage Hypothesis Valid for Developing Countries? Evidence from the Turkish Cement Industry - Seref Saygili (University of Kent, Department of Economics, 1998)
The efficiency wage hypothesis is tested by using one of the recently developed methods to measure technical efficiency. We use panel data on 40 Turkish cement plants for the period 1980-1995. The predictions of the efficiency wage hypothesis are tested in two ways: estimation of wage augmented production frontiers and the simultaneous estimation of a production function together with inefficiency effects. Our empirical analysis shows that the wage level is one of the significant factors contributing to the output and technical efficiency of plants in the cement industry in Turkey.
Keywords: C12; C13; C24; J41; 330; Efficiency Wage; Stochastic Production Function with Composed Errors; Technical Efficiency; Effizienzlohn; Schätzung; Zementindustrie; Türkei